EDITOR DE LA REVISTA: ENTRE EL SUEÑO Y LA SUPERVIVENCIA - Maria das Graças TARGINO,Joana Coeli RIBEIRO GARCIA (Fonseca, Journal of Communication, 2023)
Analyzes the role of scientific editor, lists the skills needed for those yearning to be editor and resumes his functions in a scientific journal. Review the main concepts such as editor and publisher, editing and publishing process.